The Association Between Physical Activity And Menstrual Cycle Regularity In Female Students - Anggun Novia Ramadhani; Satwika Arya Pratama; Fitriana Nugraheni; Nur Anindya Syamsudi (CV. AFDIFAL MAJU BERKAH, 2026)
Menstrual cycle irregularity remains a common reproductive health problem among adolescent girls and women of reproductive age, and it may be influenced by factors such as body image, physical activity, and nutritional intake. This study aimed to analyze the relationship between body image, physical activity, and nutritional intake and menstrual cycle regularity among undergraduate Nutrition students at the Faculty of Sports Science and Health, Universitas Negeri Surabaya. This study used an analytical observational design with a cross-sectional approach. A total of 78 female students were selected using a quota sampling technique. Body image data were collected using the BSQ-34, physical activity using the IPAQ-SF, and nutritional intake using the 24-hour food recall method. Data were analyzed using the Chi-Square test and Fisher's Exact Test (p<0.05). The results showed that 77% of respondents had regular menstrual cycles, 83.3% had a positive body image, and 48.7% had moderate physical activity. No significant relationship was found between body image (p=0.483) or energy intake (p=0.457), carbohydrate intake (p=0.070), protein intake (p=0.483), fat intake (p=0.982), and iron intake (p=0.367) and the menstrual cycle. However, there was a significant relationship between physical activity and the menstrual cycle (p=0.030). It can therefore be concluded that in this study only physical activity was related to menstrual cycle regularity, whereas the other variables did not show a significant relationship.